2016
DOI: 10.18178/ijtef.2016.7.2.493
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Television Commercials on Customers’ Loyalty — A Mediation Analysis of Brand Awareness

Abstract: The main objective of this study was to investigate the effects of television commercials (TVCs) on customers' loyalty through brand awareness in Ho Chi Minh City, Viet Nam. Quantitative approach was applied with structured questionnaires conveniently and directly to 300 customers of milk industry. Several statistical techniques were used such as factor analysis, multiple regressions, and path analysis. This study found that factors of TVCs including music, trust, humor, interest, advertising message, repetiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Creating and maintaining brand awareness is considered as one of the most main goals of marketing (Keller, 2013). Brand Awareness is directly associated to the strength of the brand node or trace in memory, which is measured by the consumers' ability to identify the brand under different conditions (Khuong, Hoa and Nguyen, 2016). Moreover, the study of (Khan, Jadoon and Tareen, 2016) stated that customers cannot buy any products unless brand awareness is created.…”
Section: Brand Awarenessmentioning
confidence: 99%
“…Creating and maintaining brand awareness is considered as one of the most main goals of marketing (Keller, 2013). Brand Awareness is directly associated to the strength of the brand node or trace in memory, which is measured by the consumers' ability to identify the brand under different conditions (Khuong, Hoa and Nguyen, 2016). Moreover, the study of (Khan, Jadoon and Tareen, 2016) stated that customers cannot buy any products unless brand awareness is created.…”
Section: Brand Awarenessmentioning
confidence: 99%
“…Traditionally marketers have researched and found out that loyalty does effect in a positive word of mouth thus creating a positive purchase intention among consumers. According to Khuong, Hoa, and Nguyen (2016) customer loyalty is heavily affected by trust, brand recall and interest in relation to the brand. In a recent study carried out by Khuong et al (2016) has found out that the more consumers are exposed to the advertisements by a particular brand, the more they will become loyal to that particular brand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Khuong, Hoa, and Nguyen (2016) customer loyalty is heavily affected by trust, brand recall and interest in relation to the brand. In a recent study carried out by Khuong et al (2016) has found out that the more consumers are exposed to the advertisements by a particular brand, the more they will become loyal to that particular brand. Customer loyalty is built through frequently keeping up the associations with the customers mainly through effective advertising and understanding the customer needs and wants (Oliver, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%